Adoption of robotic technology in Turkey: A nationwide analysis on caseload and platform used. Issue 1 (17th October 2018) - Esen, Eren; Aytac, Erman; Ozben, Volkan; Bas, Mustafa; Bilgin, Ismail Ahmet; Aghayeva, Afag; Baca, Bilgi; Hamzaoglu, Ismail; Karahasanoglu, Tayfun
Abstract: Background: Limited data exist regarding adoption of evolving robotic technology in surgery. This study evaluated trends and the current condition of robotic platforms in surgical specialties and general surgical subspecialties. Methods: Between January 2013 and December 2017, all robotic operations performed in Turkey were included. Results: In the study period, 13 760 robotic operations were performed at 32 hospitals. The median numbers of general surgical procedures were 43and eight cases per hospital and per general surgeon, respectively. The high‐volume general surgeons performed 1734 (81%) of the cases. Forty‐five percent and 55% of the general surgical operations were performed with the Xi and S/Si robots, respectively. Conclusion: Use of the Xi platform seems to increase caseload in general surgery operations possibly by facilitating robotic colorectal surgery. Targeting the high‐volume centres and surgeons for further training and implantation of upcoming robotic technology can be more effective in terms of increasing case volume and improving outcomes.